2013
DOI: 10.1111/ejss.12043
|View full text |Cite
|
Sign up to set email alerts
|

Measuring reactive metal in soil: a comparison of multi‐element isotopic dilution and chemical extraction

Abstract: The isotopically exchangeable metal pool (E-value) of zinc (Zn), cadmium (Cd) and lead (Pb) were simultaneously measured, using stable isotope dilution, in soils contaminated by Pb/Zn mining activities and varying in properties likely to affect metal reactivity, including pH, organic matter content, metal concentration and land use. E-values were compared with single and sequential extraction schemes. Results showed a wide range of metal reactivity (approximately 1-100% of total) depending on the extent of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 37 publications
5
38
0
Order By: Relevance
“…They suggested that high values of %Pb E in soils contaminated with smelter fallout or battery production waste may arise because the Pb from these sources is more likely to enter the soil in a relatively soluble form. Similar %Pb E values have been measured in acidic woodland and grassland soils (Marzouk et al, 2013a) whereas, in the same study, in alkaline minespoil soils with extremely high Pb concentrations (> 20,000 mg kg -1 ) %Pb E values were very low because of poorly soluble secondary carbonate or primary sulphide mineralogy; overall the range in %Pb E was 7-99% when all soils were considered. In a second study of Pb lability in a contaminated catchment, Marzouk et al (2013b) observed an inconsistent trend in %Pb E value with soil metal:.…”
Section: Introductionsupporting
confidence: 83%
“…They suggested that high values of %Pb E in soils contaminated with smelter fallout or battery production waste may arise because the Pb from these sources is more likely to enter the soil in a relatively soluble form. Similar %Pb E values have been measured in acidic woodland and grassland soils (Marzouk et al, 2013a) whereas, in the same study, in alkaline minespoil soils with extremely high Pb concentrations (> 20,000 mg kg -1 ) %Pb E values were very low because of poorly soluble secondary carbonate or primary sulphide mineralogy; overall the range in %Pb E was 7-99% when all soils were considered. In a second study of Pb lability in a contaminated catchment, Marzouk et al (2013b) observed an inconsistent trend in %Pb E value with soil metal:.…”
Section: Introductionsupporting
confidence: 83%
“…This indicates that in calcareous soils metal releases based on equilibrium principles cannot explain plant metal uptake. As previous studies using isotope dilution techniques indicate, acid-soluble and part of oxidisable metals in soils can be released to the soil solution based on equilibrium principles (Ahnstrom and Parker, 2001;Marzouk et al, 2013). However, in this study soil reducible and oxidisable metal fractions in both acid and calcareous soils showed large decreases after phytoextraction (Figs.…”
Section: Soil Metal Processes During Phytoextractionmentioning
confidence: 43%
“…In addition, due to the low spike rate, it was difficult to accurately measure Pb isotopic ratios in the soil suspension of UMT31 and CAD; the E values of Pb in the two soils were therefore not obtained. In other words, it is better to use a larger spike rate based on the total or extractable metal concentration rather than the concentrations in solution (Marzouk et al, 2013a), especially for alkaline soil with very small metal concentrations in solution relative to their total metal contents.…”
Section: Siek Resultsmentioning
confidence: 99%